Linking Knowledge Management and Environmental Performance: A Pathway to Sustainable Competitiveness - Patnaik, Amitabh (Journal of Knowledge Management Practice, 2026)
This study looks at how important knowledge management (KM) procedures including acquisition, sharing,  storage, and application affect green innovation and help small and medium-sized businesses (SMEs) in  the IT and ITES sectors grow in a way that is good for the environment. It looks at how better managing  knowledge might improve social performance, environmental responsibility, and economic resilience. The  study's goal is to show how important KM is for promoting innovation that supports sustainability goals,  which will lead to long-term competitive advantage and responsible business practices. We used structural  equation modelling (SEM) to look at the effect of knowledge management processes on green technology,  green management innovation, and the environmental, social, and economic aspects of sustainability.  Green innovation had a big positive effect on CSD. Dimensional analysis showed that all paths except  knowledge development and acquisition had a big effect on societal sustainability. Also, managing  knowledge is thought to be just as crucial for IT service companies of all sizes. No one has looked into this  in the field of research previously.
Keywords: knowledge management; sustainability; green management innovation; green environment; green technological innovation; organizational strategy